Trend of the market and the production of organic products in Peru - Campos, Manuel (2017)
$ 81.6 billion, the largest markets for organic products are United States of America, Germany and France. Regarding production, 50.9 million hectares were cultivated and 2.4 million producers worldwide participated in this activity. In Peru for the same date obtained 327,245 hectares cultivated, 97,857 producers and had an economic turn of US $ 16.6 million with a per capita consumption of US $ 0.54. Taking this context of economic and productive growth in organic production in the world and Peru, the objective of this work is to analyze the market and organic production in Peru and to show trends in comparison to the world market. To reach the objective, the methodology used was an analysis of secondary data offered by public and private institutions working directly with this sector. The data collected and used are from the most representative countries in the different topics to be analyzed and are referring to the period from 2011 to 2015. The results of this work show that throughout this period, Peru had a similar behavior of growth that the countries with greater participation in the productive sector is this in the increase of the use of the land and the participation of the producers. However, for not having updated data for this period in the economic and market sector can not be sure what behavior Peru had in these issues.